Functional Mn-Mg-k cation complexes in GaN featured by Raman spectroscopy - Devillers, T.; Leite, D. M. G. [UNESP]; Silva, José Humberto Dias da [UNESP]; Bonanni, A. (American Institute of Physics (AIP), 2013)
The evolution of the optical branch in the Raman spectra of (Ga, Mn)N:Mg epitaxial layers as a function of the Mn and Mg concentrations, reveals the interplay between the two dopants. We demonstrate that the various Mn-Mg-induced vibrational modes can be understood in the picture of functional Mn-Mgk complexes formed when substitutional Mn cations are bound to k substitutional Mg through nitrogen atoms, the number of ligands k being driven by the ratio between the Mg and the Mn concentrations. (C) 2013 Author(s).